Detection of influenza and non-influenza respiratory viruses in lower respiratory tract specimens among hospitalized adult patients and analysis of the clinical outcome - Ching-Hao Hsu; Hsin-Pai Chen; Po-Liang Chen; Yu-Jiun Chan (Journal of Microbiology, Immunology and Infection, 2022)
Background: Lower respiratory tract infection (LRTI) is one of the most fatal diseases for adults. Influenza is a well-recognized cause of severe pneumonia; however, the outcomes of LRTI caused by non-influenza respiratory viruses (NIRVs) have not been sufficiently investigated. This study aimed to describe the characteristics and outcomes of LRTI associated with respiratory viruses (RVs) in adults. Materials/methods: A retrospective review was performed using medical records of adult patients whose lower respiratory tract (LRT) specimens (endotracheal aspirate and bronchoalveolar lavage fluid) tested positive for RVs using multiplex PCR. Underlying comorbidities, laboratory data, and clinical outcomes were analyzed. Results: Among the 808 LRT specimens collected from 666 adult patients, RV was identified in 115 specimens (14%) from 106 patients (16%). The underlying comorbidities and laboratory data did not differ between patients with influenza- and NIRV-related LRTI. The 14-day and 30-day mortality rates were higher in the influenza group than in the NIRV group (24% versus 7%, p = 0.03 and 33% versus 13%, p = 0.02, respectively), whereas the 90-day mortality rate did not. In a multivariate Cox model to predict 90-day mortality, shock and acute kidney injury independently predicted a higher mortality rate (hazard ratio (HR): 4.28, 95% CI: 1.46–12.58, p = 0.01 and HR: 2.80, 95% CI: 1.28–6.15, p = 0.01, respectively), whereas the detection of influenza did not. Conclusions: Influenza and NIRVs were associated with increased mortality due to LRTI in adults. Therefore, NIRVs are among key pathogens causing LRTI and should not be neglected by clinicians.